PENGARUH PENERAPAN MODEL STAD TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK - Justen Seftian; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to analyze the effect of the STAD model on student learning outcomes in thematic learning in grade IV elementary schools. Experimental method with Quasi Experimental Design design and non equivalent control group design. Population study with a total of 59 students. The data collection technique in this research is measurement technique. The data collection tool used was a multiple choice written test. The results of hypothesis testing using t-test (Polled Variance) obtained tcount = 2.71 while for dk (29 + 29-2 = 56) with a significant level α = 5% obtained t table = 1.67, which means tcount> ttable, then Ha accepted, this proves that there is an effect of the application of the Student Team Achievement Division model in thematic learning. Based on the results of the calculation of the effect size (ES), it was found that ES = 0.73 which was included in the moderate criteria. Thus it can be said that the application of the Model Student Team Achievement Division model in thematic learning has a positive effect on the learning outcomes of fourth grade students of Elementary School 54 West Pontianak.